Clinical effectiveness of pit and fissure sealants in primary and permanent teeth of children and adolescents: an umbrella review - Amend, S.; Boutsiouki, C.; Winter, J.; Kloukos, D.; Frankenberger, R.; Krämer, N.; Justus Liebig University Giessen (My University, 2024)
Purpose: This umbrella review aimed to critically appraise the evidence published in systematic reviews (SRs) on the clinical effectiveness of sealants compared with each other/the non-use in primary/permanent teeth of children and adolescents with at least 12-month follow-up. Methods: A systematic literature search on 4 electronic databases was conducted up to January 18th, 2023. Following handsearching, two review authors independently screened retrieved articles, extracted data, and assessed the risk of bias (RoB) using the risk of bias in systematic reviews (ROBIS) tool. Based on a citation matrix, the overlap was interpreted by the corrected covered area (CCA). Results: Of 239 retrieved records, 7 SRs met the eligibility criteria with a moderate overlap among them (CCA = 7.4%). For primary molars, in 1120 1.5- to 8-year-old children, data on the clinical effectiveness of sealants were inconclusive. For permanent molars, 3 SRs found a significant caries risk reduction for sealants versus non-use (≤ 36-month follow-up). There was insufficient evidence to proof superiority of sealants over fluoride varnish for caries prevention (3 SRs), and to rank sealant materials according to the best clinical effectiveness in permanent molars. One study was rated at low and 6 at high RoB, which did not allow for a valid quantitative synthesis. Conclusion: Considering the limitations of this umbrella review, sealants are more effective for caries prevention in children’s permanent molars compared to no treatment. Future well-implemented RCTs are needed to draw reliable conclusions on the clinical effectiveness of sealants in primary and permanent teeth of children and adolescents.
Keywords: ddc:610